Re: Andrea Necchi, Félix Guerrero-Ramos, Paul L. Crispen, et al. Gemcitabine Intravesical System plus Cetrelimab or Cetrelimab Alone as Neoadjuvant Therapy in Patients with MIBC: Primary Analysis and Biomarker Results of SunRISe-4. J Clin Oncol. In press. https://doi.org/10.1200/JCO-25-02382 - Giuseppe Di Lorenzo; Carlo Buonerba (European Urology Oncology, 2026)
Purpose Persistent smoking among patients diagnosed with cancer is associated with adverse clinical outcomes, yet tobacco treatment has not been integrated into community oncology settings. We conducted a trial of a virtual sustained tobacco treatment intervention across community oncology settings nationwide. Methods This randomized controlled trial compared the effectiveness of sustained telehealth counseling plus medication (virtual sustained treatment [VST]) to referral to the National Cancer Institute (NCI) quitline (enhanced usual care [EUC]) in assisting patients recently diagnosed with cancer to quit smoking. The VST group received up to 11 synchronous telehealth sessions (four weekly, four biweekly, three monthly) of motivational counseling and up to 12 weeks of free nicotine replacement therapy (NRT). Results From August 2019 to December 2022, 306 English- and Spanish-speaking patients were randomly assigned from 37 NCI Community Oncology Research Program community sites. Participants were 70.9% female; 86.3% was White; the median age was 57 years; and 45.4% had non-smoking-related tumors. A total of 221 of 302 (73.2%) smoked within 30 minutes of waking. Six-month, 7-day point abstinence rates were 28.4% (42 of 148) in the VST group versus 14.7% (21 of 143) in the EUC group; there were no significant treatment moderators. A total of 80.8% (126 of 156) of VST participants engaged in counseling, and 85.7% (108 of 126) were dispensed NRT. Participants who completed >8 sessions versus <5 sessions were more likely to quit; P = .005. VST participants were almost four times more likely to report guideline-concordant smoking cessation medication use. Continuous abstinence and significant reduction rates at 6 months were higher in the VST group. The incremental cost per quit was $7,724 in US dollars. Conclusion Among recently diagnosed patients, sustained remotely delivered telehealth counseling and free NRT were well utilized and nearly doubled 6-month quit rates compared with EUC. Findings support the benefit of adopting sustained tobacco treatment within community oncology care settings nationwide.